Modern free-trade agreements and the rise of populism - Nahtigal, Matjaž (Teorija in praksa, 2019)
The difference between the post-war development of international legal trade regimes and the context of the latest free-trade initiatives is that the disparate effects of trade liberalisation have also become visible in the most advanced economies in the world, including the United States and the European Union, not only in developing countries. This trend requires a rethinking of trade arrangements that would provide suitable instruments, tools and policies when needed for restructuring. The key challenge in the process of deepening and widening the economic and legal integration is how to disseminate the economic, technological, financial and other benefits to those regions and parts of the population that are currently excluded. In order to overcome this negative trend, comprehensive efforts to disseminate the benefits as widely as possible should be applied at the local, national and international levels.
Keywords: Agreements; Free trade; International trade; Mednarodna trgovina; Prosta trgovina; Sporazumi